2023
DOI: 10.24093/awej/comm1.10
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Intercultural Communicative Competence and Student Autonomy through Project-Based Learning

Abstract: In today’s internationalized learning environment, intercultural communicative competence is deemed insufficient for students. Academic mobility presents challenges and opportunities due to language, culture, and learning background differences. The number of international students in Ukrainian universities is increasing. The efficacy of project-based learning in foreign language acquisition is recognized and incorporated into the English language syllabus in Ukraine. The current study investigates the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In previous studies, Global Project-based Learnings (gPBLs) have been shown to be effective from both quantitative and qualitative perspectives [6], [7]. However, several issues with the gPBL format have also been identified [8], [9].…”
Section: Issues With Sit's Online Gpbls Identified In Ay2020 and Resu...mentioning
confidence: 99%
“…In previous studies, Global Project-based Learnings (gPBLs) have been shown to be effective from both quantitative and qualitative perspectives [6], [7]. However, several issues with the gPBL format have also been identified [8], [9].…”
Section: Issues With Sit's Online Gpbls Identified In Ay2020 and Resu...mentioning
confidence: 99%